Lembar Kerja Siswa Berbasis ICT Sebagai Solusi Kegiatan Latihan Pembelajaran Mandiri - Kuntum Annisa Imania (JURNAL PETIK, 2016)
The main problem in this paper is focused on the useof ICT based on students’ worksheet as a solution in learningactivities. The achievement of students’ learning outcomes isnot easy to be solved the main problem (the root of theproblem). One of which is to train students with exercises, thena collection of exercises is widely used by educators (teachers)in the form of print media or hard copy called LKS, butunfortunately sometimes the presence of LKS is generally onlya set of questions that monotony which often lead to boredom,so that students become lazy in working the exercises.Sometimes the serving method of students’ worksheet alsomonotonous and less varied. The student worksheet thatcontains questions of subjects may be categorized as subjectsless desirable by the students such as, math, English or science.If the serving method of students’ worksheet are notaccompanied by variations, the students will get bored andunwilling to understand the questions.With the presence of LKS based ICT can address allthe needs of students and teachers in implementing thelearning activities to be more variety, innovative and able toenhance students' creativity. In addition, in the terms of time itis more flexible, because of the presence of ICT-basedworksheets students are able to do the exercises wherever theyare, as long as they were able to connect with the Internetnetwork and can access it.The model of ICT based on interactive of the collection ofexercises (LKS) is different from the collection of exercises(LKS) circulated in the schools. This LKS based on ICTinteractive worksheets are used to deliver the material into aseries of questions as an introduction to learners inconstructing their understanding. The series of questions toeach other are interconnected. So that students have to learnthe use of these worksheets in a coherent from beginning toend of materials. The learners learn the material presentedthrough questioning so that the formula or concept was foundby the learners.